From the Cognitive Stage to the Zone of Proximal Development: A Theoretical Synthesis of Piaget and Vygotsky in the Perspective of Educational Psychology - Hamidalloh, Ahmad Sayyidiman; Muhid, Abdul; Rofiq, Arif Ainur; Permadi, Muhammad Syafrani Surya; Saifullah, Dimas Ahmad (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The development of 21st-century education demands learning that is not solely oriented toward the transmission of knowledge, but also toward the development of higher-order thinking skills integrated with the social dynamics of students. In educational psychology, cognitive development theory and sociocultural theory are often positioned dichotomously: internal structure versus social mediation. This article aims to formulate a theoretical synthesis that integrates these two perspectives into a complementary and operational developmental model. The research employed a qualitative approach with library research. Data were obtained from primary works and relevant, reputable scientific literature, then analyzed using content analysis and comparative-critical analysis techniques to identify epistemological assumptions, common ground, and limitations of each theory. The results indicate that the structure of cognitive development serves as an indicator of epistemic readiness to learn, while the Zone of Proximal Development acts as an acceleration mechanism through social mediation and adaptive scaffolding. This synthesis yields a dynamic and cyclical Integrative Model of Cognitive-Social Development, in which social interactions encourage cognitive restructuring and shape new readiness at a higher level.